Collective Efficacy as a Mediator of the Trustworthiness – Performance Relationship in Computer-Mediated Team-based Contexts. Issue 7 (3rd October 2019) - Capiola, August; Alarcon, Gene M.; Lyons, Joseph B.; Ryan, Tyler J.; Schneider, Tamera R.
Abstract: The current study investigated the role of trustworthiness perceptions at the individual level and collective efficacy at the team level on team performance in computer-mediated teams using multi-level structural equation modeling (MSEM). It was hypothesized that trustworthiness perceptions and collective efficacy would predict team performance, and collective efficacy would partially mediate the trustworthiness – performance relationship in computer-mediated teams. Sixty-four teams (five participants each) engaged in a computer-mediated task across two experimental sessions. Trustworthiness measured after session 1, collective efficacy measured after sessions 1 and 2, and team performance measured of sessions 1 and 2 were used to build the MSEM. The half longitudinal model for assessing mediation was used to examine the influence of trustworthiness perceptions on performance through collective efficacy over time. Results demonstrated support for the hypothesized model, such that trustworthiness perceptions demonstrated indirect effects on performance through collective efficacy. These findings extend past research by identifying an emergent mechanism by which trustworthiness is important for team performance in computer-mediated teams.